Lipid Emulsion for Local Anesthetic Systemic Toxicity - Sarah Ciechanowicz; Vinod Patil (Anesthesiology Research and Practice)
The accidental overdose of local anesthetics may prove fatal. The commonly used amide local anesthetics have varying adverse effects on the myocardium, and beyond a certain dose all are capable of causing death. Local anesthetics are the most frequently used drugs amongst anesthetists and although uncommon, local anaesthetic systemic toxicity accounts for a high proportion of mortality, with local anaesthetic-induced cardiac arrest particularly resistant to standard resuscitation methods. Over the last decade, there has been convincing evidence of intravenous lipid emulsions as a rescue in local anesthetic-cardiotoxicity, and anesthetic organisations, over the globe have developed guidelines on the use of this drug. Despite this, awareness amongst practitioners appears to be lacking. All who use local anesthetics in their practice should have an appreciation of patients at high risk of toxicity, early symptoms and signs of toxicity, preventative measures when using local anesthetics, and the initial management of systemic toxicity with intravenous lipid emulsion. In this paper we intend to discuss the pharmacology and pathophysiology of local anesthetics and toxicity, and the rationale for lipid emulsion therapy.